Bandwidth simulation as a monte carlo queuing system - Ali Hadian; Mehri Bagheian; Behrouz Fathi Vajargah; Sayyed Saeid Ayat (Journal of Hyperstructures, 2018)
One of the issues raised in cloud computing is the datacenter locating problem and one of the effective factors in designing data center locations is amount of data volume and referrals to it. This depends on the number of customers or users who are going to use that data center, which is a probable issue. In this paper, the bandwidth simulation is described by considering the bandwidth system as a queuing system and simulating it by Monte Carlo method. We explain how to simulate the bandwidth consumption in different static and dynamic simulation states for a real computer system and we show that the bandwidth required at an Endpoint in cloud computing can be calculated with different Gamma distribution parameters.